Naphthalenone polyketides produced by Neofusicoccum parvum, a fungus associated with grapevine Botryosphaeria dieback - BURRUANO, Santella; GIAMBRA, Selene; MONDELLO, Vincenzo; DELLAGRECA, Marina; BASSO, Sara; TUZI, Angela; ANDOLFI, Anna (Phytopathologia Mediterranea, 2016)
A strain of Neofusicoccum parvum isolated from declining vines was pathogenic to grapevine cultivar Inzolia in Sicily. This strain produced some metabolites in liquid medium. Crude extract, through a bio-guided purification process, yielded four naphthalenone polyketides. They were identified by comparison with spectroscopic data and optical proprieties reported in literature as: (3S, 4S)-7-ethyl-3,4,8-trihydroxy-6-methoxy-3,4-dihydro-1-(2H)-naphthalenone, (3S*, 4S*)-3,4-dihydro-3,4,8-trihydroxy-7-(1-hydroxyethyl)-6-methoxy-1-(2H)-naphthalenone, (4S)-3,4-dihydro-4,8-dihydroxy-1-(2H)-naphthalenone, named botryosphaerones D and A, isosclerone, respectively, and (3S*,4S*)-3,4,5-trihydroxy-1-tetralone (1-4). Phytotoxic activity of the isolated compounds (1-4) was tested on grapevine leaves at using the leaf puncture assay. All tested compounds were phytotoxic, with botryosphaerone D showing the greatest activity. The phytotoxic effects decreased when treated leaves were exposed to light. All of the metabolites did not show in vitro antifungal activity against Diplodia seriata, Lasiodiplodia mediterranea, Neofusicoccum vitifusiforme, or Phytophthora citrophthora. This is the first report of in vitro production of botryosphaerones D and A, and 3,4,5-trihydroxy-1-tetralone by N. parvum.